Genuine halitosis in patients with dental and laryngological etiologies of mouth odor: severity and role of oral hygiene behaviors. (2nd February 2018) - Herman, Sabina; Lisowska, Grażyna; Herman, Joanna; Wojtyna, Ewa; Misiołek, Maciej
Abstract : The aims of the study were to determine the severity of halitosis and the association between oral hygiene practices and the severity of malodor in patients with dental and laryngological etiologies of genuine halitosis. Thirty‐five laryngological and 40 dental patients with halitosis completed a structured interview and underwent laryngological and dental examinations. Halitosis was assessed using organoleptic and halimeter tests. Greater halitosis severity in laryngological patients was associated with worse clinical status of the palatine tonsils, less frequent toothbrushing, less frequent use of tongue cleaners, fewer daily meals, and increased use of mouthrinses. Among dental patients, more severe halitosis was associated with worse clinical status of the periodontium, more tongue coating, less saliva secretion, and less frequent use of dental floss, interdental toothbrushes, and tongue cleaners. Oral hygiene was found to be a key moderator of the relationship between status of the periodontium or tonsils and severity of halitosis. The severity of halitosis in laryngological patients and dental patients is essentially similar; however, oral hygiene routines are associated with different effects in each group. Consequently, individual recommendations for patients with halitosis should be adjusted for the underlying disease and emphasize the role of effective specific hygiene behaviors.